ЭЛЕКТРОН ТАЪЛИМ РЕСУРСЛАРИ ВОСИТАСИДА АХБОРОТ ТЕХНОЛОГИЯЛАРИНИ КАСБИЙ ФАОЛИЯТГА ЙЎНАЛТИРИБ ЎҚИТИШНИНГ ДИДАКТИК ИМКОНИЯТЛАРИ - Алламбергенова, M.X. (SCIENCE and SOCIETY, 2024)
This article discusses the creation of electronic learning resources and its didactic significance today.
Keywords: electronic resources; information technology; professional activities; electronic aids; video lessons; didactic tools